Pengaruh Partisipasi Penyusunan Anggaran, Pemahaman Akuntansi Pemerintahan dan Budaya Organisasi Terhadap Kinerja Manajerial pada Pemerintah Aceh - Saiful Bahgia (Jurnal EMT KITA, 2020)
This study aimed to examine the effect of budget participation, understanding of governmental accounting and organizational culture on managerial performance in the Aceh government. This study is a population census since all members as respondents. The population around the head SKPA (Budget Administrator / PA) Finance and Administration Officer (PPK-SKPA) which amounted to 74 respondents. The analytical tool used is multiple linear regression analysis using SPSS. The results showed that all three independent variables, namely budgetary participation, understanding of governmental accounting and organizational culture either jointly or partially affect the dependent variable is managerial performance in the Aceh government.